2018
DOI: 10.1002/mds3.10001
|View full text |Cite
|
Sign up to set email alerts
|

Organic electronics incorporating crown ethers as Na+ binding elements, towards a simple printable hydration sensor

Abstract: Here, we present the development of organic electronic sensors containing crown ethers as ion binding elements for application in Na+ detection for health monitoring. The design, fabrication and characterization of chemiresistor‐based sensors using simple solution processing methods amenable to printing were demonstrated. The analyte testing comprised aqueous solutions of sodium chloride (0, 20, 50, 80 and 130 mM), with the Na+ concentration reflecting the range which occurs in human sweat. The introduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Graphene-based tattoos are patterned in serpentine structures through a wet-transfer dry-pattering approach. Organic materials containing a linked chain of crown ether were printed as Na + -binding elements for the development of a simple hydration sensor [ 119 ]. The ideal polymeric molecule containing a linked chain of crown ether is poly[(dibenzo-18-crown-6)-co-formaldehyde], which was evaluated by comparing the device characteristics with a reference device without the crown ether.…”
Section: Wearable Sensorsmentioning
confidence: 99%
“…Graphene-based tattoos are patterned in serpentine structures through a wet-transfer dry-pattering approach. Organic materials containing a linked chain of crown ether were printed as Na + -binding elements for the development of a simple hydration sensor [ 119 ]. The ideal polymeric molecule containing a linked chain of crown ether is poly[(dibenzo-18-crown-6)-co-formaldehyde], which was evaluated by comparing the device characteristics with a reference device without the crown ether.…”
Section: Wearable Sensorsmentioning
confidence: 99%
“…The comparatively straightforward synthesis and availability of monomer has for some time positioned P3HT among a limited group of donor polymers that are suitable for the large-scale commercialisation of OPVs [66]. The hole mobility of P3HT has been shown to be tunable across the range of 10 −4 -10 −1 cm 2 V −1 s −1 by controlling the molecular weight [66,67], regioregularity [68] and interchain polarity through organic acid dopants [69], leading to applications in transistors and sensors [70] where the output sensitivity is dependent on these doping mechanisms. Electroactive P3HT inks have also been shown to have their electronic and ionic conductivity modulated by the local humidity and polyionic additives [71].…”
Section: Semiconducting Polymersmentioning
confidence: 99%
“…Because the organic semiconductors are so susceptible to small changes in ionic dopant content, they act as voltage transducers with low bias voltages (∼1 to 10 V) and very high sensitivity which can be modulated by controlling the nanostructure of the dielectric using the solvent washing technique described in the previous section. At the University of Newcastle, we have previously demonstrated printable organic biosensors based on both an enzyme-containing OTFT for glucose sensing [123], and a crown-ether-modified chemiresistor for sodium ion sensing [70] that operate on the same principles. The group of Bortolotti has demonstrated the successful fabrication of a tumour necrosis factor alpha (TNFα) sensors using anti-TNFα as a recognition element grafted on to the gate electrode of the transistor [241], while Magliulo et al demonstrated another similar type of device, this time with the recognition element (anti-C-reactive protein monoclonal antibody) bound to the semiconductor layer rather than the gate electrode [242].…”
Section: Printed Biofunctional Sensorsmentioning
confidence: 99%